Особливості кримінологічної характеристики шахрайства, що вчиняється організованою групою - Недзельська , Галина Всеволодівна (My University, 2022)
У дисертації проведено аналіз кримінологічної характеристики шахрайства, що вчиняється організованою групою, здійснено розробку науково обґрунтованих заходів, спрямованих на усунення пов’язаних із ним проблем правозастосовної практики й удосконалення правового механізму запобігання зазначеному суспільно небезпечному діянню. Проаналізовано історію розвитку поняття «шахрайство» на тлі вітчизняного та міжнародного законодавства. Розкрито зміст шахрайства, що вчиняється організованою групою, і надано характеристику його системоутворюючих ознак. Проаналізовано стан, рівень та інші кримінологічно значущі ознаки шахрайства, що вчиняється організованою групою. Запропоновано кримінологічну характеристику особи, що вчиняє шахрайство у складі організованої групи, з’ясовано причини та умови, які сприяють вчиненню шахрайства у складі організованої групи. Досліджено загальносоціальні, спеціально-кримінологічні заходи запобігання шахрайству, що вчиняється організованою групою. Роз’яснено віктимологічну профілактику шахрайства, що вчиняється організованою групою. В диссертации проведен анализ криминологической характеристики мошенничества, совершаемого организованной группой, научно обоснованных мероприятий, направленных на устранение в связи с этим проблем правоприменительной практики и усовершенствование правового механизма предотвращения указанного общественно-опасного деяния. Проанализирована история развития понятия «мошенничество» на фоне отечественного и международного законодательства. Определено содержание понятия мошенничества, совершаемого организованной группой и предоставлено характеристику его системообразующих признаков. Проанализировано состояние, уровень и другие криминологически значимые признаки мошенничества, совершаемого организованной группой. Проведена криминологическая характеристика лица, совершающего мошенничество в составе организованной группы, а также причины и условия, способствующие совершению мошенничества в составе организованной группы. Проанализированы общесоциальные, специально-криминологические меры по предотвращению мошенничества, совершаемого организованной группой. Исследована виктимологическая профилактика мошенничества, совершаемого организованной группой. The dissertation analyzes the state, level, and other criminologically significant features of fraud committed by an organized crime group, as well as the development ofthe main directions and ways of improving activities aimed at preventing unlawful actions in the given field. As a result of the research performed, certain scientific and theoretical conclusions were drawn, and they are important both for academic activity and for the activities of law enforcement agencies. The history of the development of the concept of «fraud» against the background of national and international legislation is investigated. The content of fraud committed by an organized group is clarified and its system-forming features are characterized. The state, level and other criminologically significant signs of fraud committed by an organized group are analyzed. The criminological characteristics of a person committing fraud in an organized group, as well as the causes and conditions that contribute to the commission of fraud in an organized group are proposed. The general social, special criminological measures to prevent fraud committed by an organized group are investigated. The victimological prevention of fraud committed by an organized group is explained. The causes and conditions for committing fraud by an organized crime group have been revealed (economic factors (low income, unemployment, high decile dispersion ratio, etc.): lack of general ideological policy and national idea, high level of legal nihilism, negative influence of mass media, influence of corruption schemes). It has been proven that modern organized fraud is a vivid example of selfdetermination of crime towards criminal specialization deepening, expanding organizational, technical, intellectual and financial resources for committing crimes and complicating the structure of groups, including through the involvement of highly qualified specialists in criminal activity. It has been found that a lot of states distinguish different types of fraud, such as: computer fraud, fraud in the field of public supplies, large-scale fraud or fraud related to obtaining drugs, psychotropic, potent, poisonous or radioactive substances, explosives substances, firearms or ammunition; insurance fraud. And interestingly, Section XXV «Deception» of the Criminal Code of the Netherlands includes 18 articles specifying all types of crimes committed by deception. It has been analyzed that the changes in the context of the definition of the «fraud» concept, as well as regarding the fact of committing by an organized group (Part 4 of Article 190 of the Criminal Code of Ukraine «Large-scale fraud or fraud committed by an organized crime group») correspond to the original version of the Criminal Code of Ukraine. It has been found that organized fraud is characterized by: careful and early preparation for the commission of crime by choosing the place and time of its commission, finding tools and means, accomplices, gathering information about the victim or victims; mandatory existence of general management and organizational beginning with mandatory subordination to a single plan; the presence of a single scheme of actions of the participants in a multi-way combination; the possibility of positional (tactical) losses for strategic victory; flexibility in the choice of means of influence on the victim (victims): misleading by deception, falsification on documentary, evidential or psychophysiological level, overcoming the victim's resistance by means of psychological and mental violence (hypnotic influence, role management techniques, blackmail or intimidation using another dependent position of the victim). It has been found that the lack of a general ideological policy and national idea, high level of legal nihilism, negative influence of the mass media, etc. also influence the growth of organized fraud. Currently, in Ukraine, there is a general situation of the greatest promotion of the cult of enrichment into people's consciousness. Committing fraud as part of an organized crime group starts to be perceived as a type of economic activity, a source of income and a way of showing one's mental and acting abilities. It has been proven that modern organized fraud is a vivid example of selfdetermination of crime towards criminal specialization deepening, expanding organizational, technical, intellectual and financial resources for committing crimes and complicating the structure of groups, including through the involvement of highly qualified specialists in criminal activity. In addition, it is an example of the creation of structures parallel to society and authorities with their own internal code of conduct, a set of values, a hierarchy and a clear division of roles. It has been established that the general social prevention of fraud committed by organized crime groups can be effective only if the following conditions are observed: every social, political or economic measure must be based on the results of systematic sociological research and legislation monitoring; it should be systemic and carried out within the framework of agreed programs and strategies of national and regional development; preventive activities must have goals, tasks and the necessary material resources; general social crime prevention involves the joint activity of authorities at all levels with the involvement of individuals and legal entities, as well as the essential participation of the mass media.
Особенности криминологической характеристики мошенничества, совершаемого организованной группой
Peculiarities of criminological characteristics of fraud committed by an organized crime group
Keywords: шахрайство, організована група, кримінологічна характеристика, жертва, запобігання, загальносоціальні заходи, спеціальнокримінологічні заходи, мошенничество, организованная группа, криминологическая характеристика, жертва, предотвращение, общесоциальные мероприятия, специально криминологические мероприятия, fraud, organized group, criminological characteristics, victim, prevention, general social measures, special criminological measures